2004
DOI: 10.2337/diabetes.53.12.3201
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Sarcoplasmic Reticulum Activity and Contractility in Diabetic db/db Mouse Heart

Abstract: Although it is known that insulin-dependent (type 1) diabetes results in depressed contractile performance associated with diminished sarcoendoplasmic reticular Ca 2؉ -ATPase (SERCA2a) activity, findings in insulinresistant (type 2) diabetes suggest a less clear association. The db/db insulin-resistant mouse model exhibits decreased cardiac performance both in situ and in isolated ex vivo working hearts. In this study, contractile performance and calcium transients were measured in Langendorff-perfused hearts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
188
4
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(216 citation statements)
references
References 42 publications
19
188
4
5
Order By: Relevance
“…In a recent study, Belke and colleagues found decreased rates of contraction, relaxation and pressure development in hyperleptinaemic Lepr/Lepr diabetic mouse hearts [44]. While cardiac mechanical findings and the slowed intracellular Ca 2+ decay in Lepr/Lepr mice are consistent with our present observation in Lep/Lep mice, Lepr/Lepr diabetic myocytes displayed significantly reduced resting and peak Ca 2+ levels [44], contrary to our finding in Lep/Lep myocytes. Decreased, increased and unchanged resting intracellular Ca 2+ levels have been seen in diabetes, insulin resistance and obesity [2,45].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In a recent study, Belke and colleagues found decreased rates of contraction, relaxation and pressure development in hyperleptinaemic Lepr/Lepr diabetic mouse hearts [44]. While cardiac mechanical findings and the slowed intracellular Ca 2+ decay in Lepr/Lepr mice are consistent with our present observation in Lep/Lep mice, Lepr/Lepr diabetic myocytes displayed significantly reduced resting and peak Ca 2+ levels [44], contrary to our finding in Lep/Lep myocytes. Decreased, increased and unchanged resting intracellular Ca 2+ levels have been seen in diabetes, insulin resistance and obesity [2,45].…”
Section: Discussionsupporting
confidence: 85%
“…Most obese or overweight individuals display enhanced rather than reduced plasma levels of leptin, contrary to the leptindeficient status in Lep/Lep obesity [4]. In a recent study, Belke and colleagues found decreased rates of contraction, relaxation and pressure development in hyperleptinaemic Lepr/Lepr diabetic mouse hearts [44]. While cardiac mechanical findings and the slowed intracellular Ca 2+ decay in Lepr/Lepr mice are consistent with our present observation in Lep/Lep mice, Lepr/Lepr diabetic myocytes displayed significantly reduced resting and peak Ca 2+ levels [44], contrary to our finding in Lep/Lep myocytes.…”
Section: Discussionmentioning
confidence: 98%
“…150 This scenario is also seen in the vast vasculature of SMT and its huge parenchyma, with an accelerated degradation of kinins by reduced release of these peptides from the working tissue. 155,156 As SMT has twenty times more mass than all tissues combined and possesses the largest vascular network, dysfunctions in this tissue will negatively impact not only the regulation of adequate energy supply in the working tissue itself, [157][158][159] but will also compromise the control of BP and glucose homeostasis in the whole organism. It is therefore not surprising that a disruption of ACE activity by these risk factors is accompanied by an exaggerated BP response during a workload 160 and by impaired insulin sensitivity in the face of a glucose challenge 161,162 (table 1).…”
mentioning
confidence: 99%
“…Due to the cardiac problems associated with rosiglitazone, and the links between hypertension, cardiac dysfunction, microvascular diabetic complications (Advani et al, 2004;Belke et al, 2004;Singh et al, 2005) (Shah et al, 2004). In a related development, Randriamboavonjy et al, (2008) also demonstrated that treatment of megakaryocytes and platelets with rosiglitazone upregulates SERCA2b.…”
Section: Rosiglitazone and Calcium Homeostasismentioning
confidence: 99%